Malaysian shopping mall behavior: an exploratory study - Ahmed, Zafar U; Ghingold, Morry; Dahari, Zainurin (Emerald Group Publishing Limited, 2007)
The ascendancy of the shopping mall as a significant shopping, social interaction and/or entertainment destination has had amajor impact on retail strategies and the retail landscape in numerous countries, especially the USA. Shopping malls are not nearly as well established in developing and newly industrialized countries, however. Hence, the purpose of this paper is to assess international consumer behavior in regards to shopping malls in a non-Western country, specifically, Malaysia.